2013
DOI: 10.1111/jawr.12133
|View full text |Cite
|
Sign up to set email alerts
|

A Multi‐Scale Analysis of Single‐Family Residential Water Use in the Phoenix Metropolitan Area

Abstract: Studies that evaluate determinants of residential water demand typically use data from a single spatial scale. Although household‐scale data are preferred, especially when econometric models are used, researchers may be limited to aggregate data. There is little, if any, empirical analysis to assess whether spatial scale may lead to ecological fallacy problems in residential water use research. Using linear mixed‐effects models, we compare the results for the relationship of single‐family water use with its de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 90 publications
2
35
0
Order By: Relevance
“…The major physical water resources for the PMA are the Colorado River via the Central Arizona Project (CAP); the Salt and Verde rivers, via the Salt River Project (SRP); and substantial, but nonrenewable groundwater underlying the PMA. The core PMA municipalities have greater access to surface water (the CAP and SRP systems), while smaller municipalities on the outskirts of the PMA are more dependent on groundwater [32], although residential water consumption trends [33] are postively correlated with income [34][35][36]. Scarce water resources coupled with precipitous growth has placed strains on the water supply system and created competition between PMA municipalities and economic sectors (industrial/commercial, residential, utilities, etc.)…”
Section: Study Areamentioning
confidence: 99%
“…The major physical water resources for the PMA are the Colorado River via the Central Arizona Project (CAP); the Salt and Verde rivers, via the Salt River Project (SRP); and substantial, but nonrenewable groundwater underlying the PMA. The core PMA municipalities have greater access to surface water (the CAP and SRP systems), while smaller municipalities on the outskirts of the PMA are more dependent on groundwater [32], although residential water consumption trends [33] are postively correlated with income [34][35][36]. Scarce water resources coupled with precipitous growth has placed strains on the water supply system and created competition between PMA municipalities and economic sectors (industrial/commercial, residential, utilities, etc.)…”
Section: Study Areamentioning
confidence: 99%
“…A substantial proportion of the literature has been focused on understanding the socioeconomic factors and physical building characteristics that impact single-family residential water use (Chang, Parandvash, & Shandas, 2010;House-Peters, Pratty, & Chang, 2010;Ouyang, Wentz, Ruddell, & Harlan, 2013;Polebitski & Palmer, 2009;Wentz & Gober, 2007). Yet, despite building typology being shown to impact water usage in several studies, there is a dearth of research examining the socioeconomic factors and physical building characteristics that impact water usage in multi-family residential buildings in dense urban areas like New York City (Domene & Saurí, 2006;Fox, McIntosh, & Jeffrey, 2009;Wentz et al, 2014;Zhang & Brown, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The aggregate water consumption data in areal units may lead to an ecological fallacy problem when the statistical analysis and conclusions based on aggregate data are not applicable on an individual scale [9,10]. Several studies have shown that domestic water consumption varies significantly according to the characteristics of the properties, and also due to different water usage behaviours found in individual households [6,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that domestic water consumption varies significantly according to the characteristics of the properties, and also due to different water usage behaviours found in individual households [6,9,11,12]. This highlights the importance of an analysis of water consumption at the level of individual households.…”
Section: Introductionmentioning
confidence: 99%